2017
DOI: 10.1002/2016gl071668
|View full text |Cite
|
Sign up to set email alerts
|

Further intensification of deep convection in the Labrador Sea in 2016

Abstract: There has been a progressive deepening of winter convection in the Labrador Sea since 2012, with the individual profile maximum depth exceeding 1800 m since 2014 and reaching 2100 m in 2016. This increase, during repeated positive phases of the winter North Atlantic Oscillation (NAO), resembles that during the formation of the record depth (2500 m) Labrador Sea Water (LSW) class in 1987–1994, attributed to repeated positive NAO forcing having provided critical preconditioning. The 2012–2016 LSW class is one of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
168
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 138 publications
(186 citation statements)
references
References 52 publications
18
168
0
Order By: Relevance
“…2.3) (e.g. Hansen et al, 2016;Yashayaev and Loder, 2017). For alternative comparative purposes, the water mass distribution using the same SWT properties as in García-Ibáñez et al (2015) is given in Fig.…”
Section: Water Mass Volume Transports For 2014mentioning
confidence: 99%
See 3 more Smart Citations
“…2.3) (e.g. Hansen et al, 2016;Yashayaev and Loder, 2017). For alternative comparative purposes, the water mass distribution using the same SWT properties as in García-Ibáñez et al (2015) is given in Fig.…”
Section: Water Mass Volume Transports For 2014mentioning
confidence: 99%
“…This water mass redistribution responds both to the salinization of LSW (e.g. Yashayaev and Loder, 2017), and to the lower density of LSW formed in recent years that occupies shallower positions in the water column. García-Ibáñez et al (2015) also reported how the progressive salinization of LSW since the late 1990s resulted in a progressive decrease in LSW and increase in ISOW.…”
Section: Water Mass Volume Transports For 2014mentioning
confidence: 99%
See 2 more Smart Citations
“…As an alternative to dividing LSW into upper and deep classes, LSW can be split into year‐classes based on their history of formation and evolution. Four distinct LSW classes have been identified in the last three decades: LSW 1987–1994 , LSW 2000–2003 , LSW 2008 , and LSW 2012–2016 [ Lazier et al ., ; Yashayaev , ; Yashayaev and Loder , ]. In general, the density of a particular LSW class corresponds with the strength and persistence of winter cooling incurred through the years of its formation.…”
Section: Introductionmentioning
confidence: 99%